Agile governance post job transformation to improve work culture in Denpasar City - Made Dwi Astika Tajem; I Nyoman Subanda (Publisia: Jurnal Ilmu Administrasi Publik, 2025)
Position Simplification or Position Transformation in government bureaucracy is a bureaucracy that is dynamic, agile and flexible, and responsive to change, and will be able to become a catalyst for development in a disruptive era. The performing and professional State Civil Apparatus (ASN) is also the main element in the field of Human Resources (HR) in realizing the achievement of national development goals. This research aims to determine the application of Agile Governance after job transformation to improve work culture in the Denpasar City Government and to determine the supporting and inhibiting factors of Agile Governance after job transformation to improve work culture in the Denpasar City Government. This research uses a qualitative descriptive approach using observation, interview, and documentation data collection techniques.  The research conclusions show that the Denpasar City Government has implemented job transformation. Governance, business processes, aspects of community participation and involvement, encouragement of rapid success, rapid and systematic change, rapid increase in results, self-motivated work culture, and moral work culture are indicators that support the Denpasar City Regional Secretariat in realizing Agile Governance. Insufficient infrastructure, human resource capabilities in using ICT, and unstable internet connections are obstacles to realizing Agile governance. Post-job transformation to improve work culture in the Denpasar City Government.